Analisis Potensi Wilayah Sebagai Pusat Pertumbuhan Dan Pelayanan Di Kabupaten Balangan Provinsi Kalimantan Selatan - Saputra, Akhmad Hermawan, Drs. M. Musiyam,MTP, Dra. Umrotun, M. Si (2016)
This research was conducted in Balangan District titled "Analysis of Potential Areas for Growth and Service Center in Balangan District South Kalimantan Province". This study aims to: (1) assess the most optimal districts as a service center in Balangan District South Kalimantan Province, (2) assess the most optimal districts as centers of growth that is capable of moving the surrounding region in Balangan District South Kalimantan Province. This study uses secondary data of Balangan District 2014. Data were obtained from the Statistics Central Agency (BPS) of Balangan District. This research was conducted with the approach of quantitative and qualitative analysis in accordance with the purpose of research. Analysis of the data by using two methods: a gravity model and schallogram analysis. The results showed: the first district that is optimal to set as the region growth center of the Balangan District is Paringin Sub district. This sub district has the highest totality of appeal with the appeal total of 63.82 and a destination (sequence 1) migration and movement (mobility) the flow of money, goods and services among all sub districts in Balangan District. This district portray economy function or category hierarchy I. Second, a more optimal districts designated as a region service center of the Balangan District is Paringin Sub district. Paringin Sub district have the totality of the appeal is highest among the other districts with a total appeal of 34 and a destination (sequence I) as a service center. Keywords: optimal location, growth centers, service center.